New Textual Interpretation of "The Fall of Icarus" by William Carlos Williams (British Journal of Multidisciplinary and Advanced Studies, 2025)
The poem "Fall of Icarus "is one of the epochs making and experimental poems in terms of its stylistic composition, containing hybrid literary form based on visible and implicit imagery as an example of transformative poetry. This poem is a paint manifestation by Peter Brueghel who tries to capture rather vivid and descriptive imageries from past to the present. It is a Greek myth in which Daedalus threatens his son, Icarus, not to fly towards the sun. However, his exalted passions never deter him and finally he comes to an end by falling as his waxed wings melt down. The moments he falls down and the surrounding beside his dead body captured in the painting are also poetically captured in the poem. Different sources of textual formulations take place in the poem: Greek myth to modern experimental poetry. This poem can be interpreted from   some of the dominant traces of new textuality. It has a strong cultural and mythical element in it and therefore it tries to manipulate deeper and inner textual features. This article, in this sense, explores hidden links and textual elements for a comprehensive analysis and objective interpretation of the poem. Though painting and poetry are inter- related, they, though, use two different ways of manifestation of texts that can enrich new textual premise for interpretation. So, this article tries to analyze it from new textual interpretation taking help from prominent critics of the time like Linda Hutenchon, Richard J. Lane, and Peter Stockwell.